High temperature dimensional alterations of implant supported frameworks - Diego Klee Vasconcellos; Antonio Carlos Cardoso; Marco Antonio Bottino; Ricardo de Souza Magini; Wilson Andriani Jr (Universidade Estadual de Campinas, 2015)
The present in vitro study was designed to evaluate the effect of high temperature firing cycles used for application of porcelain veneer in the misfit of implant supported frameworks, and the effect of a pre-heating treatment on the dimensional alterations of implant supported frameworks. The investigation was conducted based on the results given by 14 nickel-chromium (06 elements) metal structures. Half of the structures formed the control group and were exposed to simulated porcelain firings. The other half formed the test group, and were submitted to a pre-heating treatment with the implant frameworks embedded in investment, before the porcelain firing simulation. The marginal misfit measurements in both groups were made before and after the porcelain firing simulation, by using a scanning electron microscope. The results were submitted to statistical analysis of variance. The multiple comparisons were made by means of the Bonferroni "t" test. For the frameworks produced in the usual manner, without the preheating treatment (control group), misfit deteriorates during the high temperature firing cycles employed for porcelain application. In the test group, pre-heating treatment did not change the final metal distortion resulting from the porcelain firing cycles, and the greatest amount of the distortion took place before the conventional porcelain firing cycles.